Various Kinds of Functional Digestive Tract Reconstruction Methods After Proximal Gastrectomy - Lu, Shuaibing; Ma, Fei; Zhang, Zhandong; Peng, Liangqun; Yang, Wei; Chai, Junhui; Liu, Chen; Ge, Fusheng; Ji, Sheqing; Luo, Suxia; Chen, Xiaobing; Hua, Yawei (Frontiers in Oncology, 2021)
The incidence of proximal gastric cancer has shown a rising trend in recent years. Surgery is still the main way to cure proximal gastric cancer. Total gastrectomy with D2 lymph node dissection was considered to be the standard procedure for proximal gastric cacncer in the past several decades. However, in recent years, many studies have confirmed that proximal gastrectomy can preserve part of the stomach function and has a better quality of life than total gastrectomy. Therefore, proximal gastrectomy is increasingly used in patients with proximal gastric cancer. Unfortunately, there are some troubles after proximal gastrectomy with traditional esophagogastrostomy. For example, the incidence of reflux esophagitis in patients who underwent proximal gastrectomy with traditional esophagogastrostomy is significantly higher than those patients who underwent total gastrectomy. To solve those problems, various functional digestive tract reconstruction methods after proximal gastrectomy have been proposed gradually. In order to provide some help for clinical treatment, in this article, we review relevant literature and new clinical developments to compare various kinds of functionl digestive tract reconstruction methods after proximal gastrectomy mainly from intraoperative status and postoperative complications aspects. After comparison and discussion, we draw the conclusion that various functional reconstruction methods have their own advantages and disadvantages, large scale high-level clinical researches are needed to choose an ideal reconstruction method in the future. Besides, in clinical practice, surgeons should combine the patient's own condition, individualized selection of the most appropriate reconstruction method.